Implementation of Computer-Based Summative Assessment - Yuli Yulianti (Postgraduate, University of Mataram, 2023)
In this current condition, SMK Negeri 1 Tanjungpandan has utilized a paper-based test as the main method of carrying out academic exams and evaluations. Nevertheless, through the rapid development of information and communication technology, various schools and educational institutions have started to switch the evaluation process using computer-based tests as a much more efficient and effective alternative. This also applies to SMKN 1 Tanjungpandan, that expect to implement a computer-based test as the substitute for paper-based tests. This study aims to describe the implementation of computer-based summative assessment at SMK Negeri 1 Tanjungpandan. The subjects in this study were school principals, vice principals for curriculum, the school management team and proctors and technicians in charge of assessment activities. The object of this study is the use of computers based tests in the implementation of summative assessments. This research is a descriptive type using a qualitative approach with the best practice method. The research data were collected by observation and interview methods. Data analysis included data presentation and drawing conclusions. The results of the research conducted shows that the computer-based summative assessment has been running well. This can be seen from the process of preparation, implementation, monitoring, evaluation, and reporting of the assessment results that proceeded smoothly. This is also supported by the readiness of human resources in performing duties as proctors and technicians, as well as adequate infrastructure for the implementation of computer-based summative assessments.